Kierkegaard exposition and critique - Hampson, Margaret Daphne 1944-; Kierkegaard, Søren 1813-1855 (Oxford University Press, 2013)
Kierkegaard is a fascinating author. Living shortly after the dawn of modernity in the Enlightenment, he restates classical Christianity in dynamic fashion. His Lutheran heritage is vital here as he places 'faith' over against 'reason'. Yet Kierkegaard also holds decidedly pre-modern epistemological presuppositions that are supportive of his endeavour.After an initial chapter on Kierkegaard's intellectual milieu, the book expounds with reference to their philosophical and historical context seven of his major texts, ranging over theological, ethical, social and political questions. A final cha